Interaction effect of inoculum type and dosage in the fermentation process on the quality of soy milk waste (SMW) for animal feed - Haryuni, Nining; Hasanah, Niswatin; Harliana, Harliana; Sikone, Hilarius Yosef (Jurnal Ilmu Peternakan Terapan, 2025)
The aim of this research is to determine the effect of the interaction between the type and dose of inoculum in fermentation to improve the quality of soy milk waste (SMW) for animal feed. This study used a completely randomized 2 x 5 factorial design. The first factor was the type of inoculum (Saccharomyces cerevisae and Rhizopus sp.) and the second factor was the inoculum dose (0, 5, 10, 15 and 20%). Each treatment was repeated 4 times. The results of statistical analysis showed that the type factor, dosage factor of the inoculum, and the interaction between the two factors had a very significant (p<0.01) effect on the quality of color, aroma, sugar concentration and alcohol concentration of SMW. In this study, the color score from SMW was found to be between 3.00-5.00; texture scores range from 1.00 to 4.50; moisture 13.23-15.03%; sugar concentration is 0.00-5.63%, and alcohol concentration ranges from 0.00-1.43%. This research can be concluded that the interaction between the type and dose of inoculum in fermentation can improve the quality of soy milk waste (SMW). The best quality was obtained when using Saccharomyces cerevisae inoculum at a dose of 15%.